Impact of COVID-19 Pandemic on Postpartum Contraceptives Method Choice (IUD vs Tubectomy) and Characteristic Aspects: A Retrospective Descriptive Study - Soetrisno; Asih Anggraeni; Siagian, Grace; Nurinasari, Hafi; Wisdayanti, Syah Rini; Sulistyowati, Sri (Indonesian Journal of Obstetrics and Gynecology, 2024)
Objective: This study aims to assess the impact of the COVID-19 pandemic on postpartum contraceptive methods. Methods: This retrospective descriptive study was conducted at a single secondary center, utilizing secondary data retrieved from medical records at the Inpatient Installation of Sebelas Maret University Hospital, Surakarta, covering the period from January 2020 to January 2022. Results: Among users of intra-uterine devices (IUDs), 85% were below 35 years old, 65% were primiparous, 67% had a history of previous injectable contraceptive use, 79% received routine antenatal care, and 51% had education below a college level. These individuals were educated about the importance of contraceptive programs during the COVID-19 pandemic. Sixty-six percent of IUD insertions were conducted via vaginal delivery, and 27% had health facilities within less than 1 km. In contrast, tubectomy contraceptive users comprised 106 patients, with the majority (54%) being aged 35 years or older, all being multiparous, and 25% tested positive for COVID-19. Among tubectomy users, 43% had a history of previous injectable contraceptive use, 85% received routine antenatal care, and 54% had education below a college level. Similar to the IUD group, they were educated about the significance of contraceptive programs during the COVID-19 pandemic. Eighty-four percent of tubectomies were performed via cesarean section, and 27% of patients lived within less than 1 km from health facilities. Conclusion: The usage rates of intra-uterine devices and tubectomy for contraceptives remained stable during the COVID-19 pandemic. However, there was a decrease in postpartum in-person visits and mobility, coupled with an increase in hospitalizations.Keywords: contraceptive; family planning; intrauterine device; tubectomy